Rolling Bearing Fault Diagnosis Based on SVM Optimized with Adaptive Quantum DE Algorithm. (17th May 2022) - Li, Yuanyuan; Sun, Qichun; Xu, Hua; Li, Xiaogang; Fang, Zhijun; Yao, Wei
Abstract : In order to optimize traditional fault diagnosis models for practical applications, a fault diagnosis model based on support vector machines optimized with the adaptive quantum differential evolution of (AQDE-SVM) is proposed in this study. First, the traditional differential evolution is rewritten based on real number encoded into a qubit encoding. Second, this study proposes an adaptive quantum rotation gate and uses this gate to update the probability amplitude of the qubits. Finally, compared with quantum genetic algorithm support vector machines (QGA-SVM) and differential evolution-support vector machines (DE-SVM), etc., the results show that the algorithm proposed in this study has a higher diagnosis accuracy and shorter running time, providing great practical engineering value in the application of rolling bearing fault diagnosis.